Wczytani w szkołę – sposób na czytelnika .......... 115 - Wilczewska, Maja (Skąd się biorą czytelnicy?, 2025)
THE ‘WCZYTANI W SZKOŁĘ’ PROJECT AS A MEANS OF GAINING READERSThe author of the article presents the project called ‘Wczytani w szkołę’ (Read Deep into School) carried out by her in K. K. Baczyński Primary School No. 11 in Gorzów Wielkopolski. The project aims at supporting pupils in graduating from the school with the help of literature and the habit of reading for pleasure and using libraries. It consists of a series of monthly encounters with various literary genres, forms of storytelling and books other than pop-culture.